Foot steps of the ancient Great Glacier of North America : a long lost document of a revolution in 19th century geological theory /: a long lost document of a revolution in 19th century geological theory. ([2015]) - Borns, H. W (Harold W.); Maasch, Kirk A (Kirk Allen)
No abstract available